PERAN PENDAMPING SOSIAL DALAM PROGRAM KELUARGA HARAPAN DI KECAMATAN SEMARANG UTARA KOTA SEMARANG - Rochmah Deiffy Amalia, Annisa; Subowo, Ari; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2024)
The Family Hope Program (PKH) provides cash assistance to underprivileged families to improve human resources quality. Social assistants play a crucial role in PKH activities, from preparation to supervision. However, challenges include a lack of public understanding, low awareness, dependency on assistance, misuse of funds, and data synchronization issues. This study analyzes the role of social assistans and the factors affecting their performance in North Semarang District using a descriptive qualitative approach and purposive sampling. Data were collected through interviews, observations, and documentation, ensuring validity through triangulation. The results of the study indicate that among the four roles of companions (facilitative, educational, representational, and technical), the most influential and needing improvement is the technical role, which requires supervision of the implementation of PKH beneficiary commitments and the use of PKH funds. Thus, there are several sub-aspects of the companion's role that have not been carried out by the PKH social companions in North Semarang District. Competence, socialization, and role behavior drive the companion's role, while role conflict and role distance inhibit it. Future steps may include strengthening the supervision of PKH implementation, particularly the implementation of PKH beneficiary commitments by re-enforcing sanctions against violations committed by PKH beneficiaries.